Teacher learning in context: The special case of rural high school teachers - Jay Paredes Scribner (Arizona State University, 2003)
Falling under the umbrella of teacher quality, professional development is an important policy issue in US public education. Understanding teacher learning and its relationship to teacher work is critical if efforts to improve teacher quality are to be successful. This article examines one overlooked context in the discourse about teacher learning and work-rural high schools. The study focuses on 20 teachers across 3 case study schools and conceptualizes the relationship between teacher learning and work according to three contexts: the core, intermediate and peripheral contexts. These contexts are explored and important features discussed.